Examining the utility of the Hamilton early warning scores (HEWS) at triage: Retrospective pilot study in a Canadian emergency department. Issue 2 (10th May 2017) - Skitch, Steven; Tam, Benjamin; Xu, Michael; McInnis, Laura; Vu, Anthony; Fox-Robichaud, Alison
ABSTRACT: Objectives: Early warning scores use vital signs to identify patients at risk of critical illness. The current study examines the Hamilton Early Warning Score (HEWS) at emergency department (ED) triage among patients who experienced a critical event during their hospitalization. HEWS was also evaluated as a predictor of sepsis. Methods: The study population included admissions to two hospitals over a 6-month period. Cases experienced a critical event defined by unplanned intensive care unit admission, cardiopulmonary resuscitation, or death. Controls were randomly selected from the database in a 2-to-1 ratio to match cases on the burden of comorbid illness. Receiver operating characteristic (ROC) curves were used to evaluate HEWS as a predictor of the likelihood of critical deterioration and sepsis. Results: The sample included 845 patients, of whom 270 experienced a critical event; 89 patients were excluded because of missing vitals. An ROC analysis indicated that HEWS at ED triage had poor discriminative ability for predicting the likelihood of experiencing a critical event 0.62 (95% CI 0.58-0.66). HEWS had a fair discriminative ability for meeting criteria for sepsis 0.77 (95% CI 0.72-0.82) and good discriminative ability for predicting the occurrence of a critical event among septic patients 0.82 (95% CI 0.75-0.90). Conclusion: This study indicates that HEWS at ED triage has limited utility for identifying patients at risk of experiencing a critical event. However, HEWS may allow earlier identification of septic patients. Prospective studies are needed to further delineate the utility of the HEWS to identify septic patients in the ED. RÉSUMÉ: Objectifs: Les scores de détection précoce reposent sur les signes vitaux pour le repérage des patients susceptibles de souffrir d'une maladie grave. L'étude décrite ici portait sur le score de détection précoce Hamilton Early Warning Score (HEWS), appliqué au moment du triage au service des urgences (SU) chez les patients ayant connu un événement grave durant leur hospitalisation. Le score HEWS a aussi fait l'objet d'évaluation comme indicateur prévisionnel de sepsie. Méthode: La population à l'étude se composait de malades admis dans deux hôpitaux, sur une période de six mois. Les « cas » étaient formés de malades ayant subi un événement grave, défini comme un séjour non prévu au service des soins intensifs, la réanimation cardiorespiratoire ou la mort. Les « témoins », de leur côté, ont été choisis au hasard dans la base de données, et ce, dans un rapport de deux pour un afin d'apparier les cas selon le fardeau des maladies concomitantes. Enfin, les chercheurs se sont appuyés sur les courbes ROC (courbes caractéristiques de la performance d'un test) pour évaluer le score HEWS comme indicateur prévisionnel d'une détérioration grave et de sepsie. Résultats: L'échantillon comptait 845 patients, dont 270 ont connu un événement grave. Quatre-vingt-neuf patients ont été écartés en raison de signes vitaux manquants. L'analyse ROC a indiqué que le score HEWS appliqué au moment du triage au SU avait une faible capacité de discrimination au regard des risques d'événements graves (0, 62; [IC à 95 % : 0, 58-0, 66]), une capacité moyenne de discrimination au regard des critères de sepsie (0, 77; [IC à 95 % : 0, 72-0, 82]) et une bonne capacité de discrimination au regard des risques d'événements graves chez les patients septicémiques (0, 82; [IC à 95 % : 0, 75-0, 90]). Conclusion: D'après les résultats de l'étude, le score HEWS appliqué au moment du triage au SU se révèle finalement peu utile dans le repérage des patients susceptibles de connaître un événement grave, bien qu'il puisse permettre la reconnaissance précoce des patients en état de septicémie. Il faudrait mener des études prospectives afin de circonscrire davantage l'utilité du score HEWS dans le repérage des patients septicémiques au SU.